An efficient SIMPLER-revised algorithm for incompressible flow with unstructured grids. (4th May 2017) - Li, Jie; Zhang, Quan; Zhai, Zhi-Qiang(John)
ABSTRACT: This paper proposes an efficient segregated solution procedure for the two-dimensional incompressible fluid flow on unstructured grids. The new algorithm is called SIMPLERR (SIMPLERR-revised algorithm). It includes an inner iterative process that consists of a pressure equation solution and an explicit velocity correction, and then, the pressure field is obtained by another solving process for the pressure equation. The features and advantages of the SIMPLERR algorithm are demonstrated by solving a benchmark flow problem, and the results indicate that the SIMPLERR algorithm can maintain a strong stability as the IDEAL algorithm and can converge faster than the SIMPLER algorithm or even than the IDEAL algorithm. The advantage of the SIMPLERR algorithm is especially evident for high-Re and fine-mesh fluid flow cases, where the SIMPLERR algorithm and the IDEAL algorithm can obtain a convergence result but the SIMPLER algorithm cannot. The SIMPLERR algorithm is about two times faster than the IDEAL algorithm.